Higher order thinking in transition : a case study of first year university students. - Dison, Laura (My University, 2010)
This thesis is a contrastive case study which explores elements of student writing in relation to higher order thinking of 12 students enrolled in a Foundation in English Course at the University of the Witwatersrand. All of the students speak English as an additional language. They were admitted to the university through an alternative admissions route that recognised their academic potential in the early 2000s. The study examines a number of factors related to students’ academic dispositions and personal qualities, their capacity to develop comparison and discursive writing and the growth in their ability to reflect on their writing tasks through the foundation year. It has developed an integrative approach for investigating contextual and courserelated issues which contributed towards students’ cognitive and meta-cognitive growth as first year university student in transition. The research methodology makes use of socio-cognitive instruments for assessing students’ levels of cognition through their writing. In particular, the SOLO taxonomy (Biggs and Collis 1982) has been adapted as a tool for analysing student responses to the different task types and for assessing student engagement with the course pedagogy and feedback practices. It uses a meta-cognitive hierarchical model (Perkins 1992) for gauging how students reflect on their writing development in response to the meta-level questions integrated into the course material. For its theoretical framework, the study draws on socio-cultural understandings of student cognition and learning, local and international research in the field of higher education as well as current developments in academic literacy and social constructivism. The implications of both the developmental and socially-based perspectives are examined in order to make sense of the pedagogical data within the Foundation Course. There is a particular focus on the range of scaffolding devices used to promote higher order thinking. A number of key findings emerge from the detailed comparative analysis of the two groups of students (‘solid’ and ‘borderline’) based on their academic performance on the Foundation Course. The most significant is the establishment of a profile of ii students who have benefited the most from the various forms of scaffolding and assessment practices on the course. The study reveals that students in the solid group show adeptness at higher order reasoning, explanation, elaboration and reflection compared to those from the borderline group who are unable to benefit optimally from the intensive interaction and mediation on the course. The analysis unpacks the intrinsic and extrinsic factors that promote or inhibit engaged learning on the course. In so doing, it highlights strengths and gaps in the pedagogical orientation of the teaching pedagogy for developing academic potential in this context. In order to address generalised, deficit views within the university about the perceived under-performance of ‘foundation students’, the study aims to present a more nuanced account of how students have engaged with academic literacy on the Foundation Course. It seeks to understand how students develop higher order thinking in the transition from school to university and have the capacity to make progress in a course in which educational strategies and assessment practices are highly scaffolded on an extended four-year degree programme. The case study methodology underlines the importance of documenting and tracking student progress more systematically and assessing the extent to which they transfer academic literacy competencies to other disciplines. The thesis investigates possibilities for integrating the educational strategies described in the thesis to promote transitional learning for first year students at university.